EFFECT OF JOB ENRICHMENT ON EMPLOYEE MOTIVATION IN SELECTED PRIVATE UNIVERSITIES IN SOUTH-WEST NIGERIA - Magaji, Nanle (Researchers World - International Refereed Social Sciences Journal, 2021)
The study is an assessment of the effect of job enrichment on non-academic staff motivation in private universities in Nigeria; a survey of selected private universities in South-western Nigeria. The main objective of the study was to investigate the relationship between job enrichment and employees’ motivation. This study employed a cross-sectional survey design. Data was collected from 547 non-academic staff and was analyzed using Descriptive Statistics (mean, standard deviation) and Regression Analysis to assess the job enrichment and motivation-rating in line with the objectives of the study. The finding revealed that there is strong positive relationship between job enrichment and employee motivation. Results showed that job enrichment account for employee motivation at 66% relationship and 44% variation at a significance level of 0.05. This shows that non- academic staff in the sampled universities are highly motivated by the practice of job enrichment design. The study recommended that human resources directors of the seven selected private universities surveyed and other organizations alike should take account of individual differences, attributes and people orientation to work. The management should not generalize the motivation strategies, rather individual should be motivated accordingly.